Pułapki rozwiązań indywidualistycznych, pułapki rozwiązań systemowych : w stronę nowej koncepcji działania ekonomicznego - Scheuer, Bartosz (Limitations of individualism, limitations of structural solutions: towards new conception of economic action, 2005)
Theory of economics is based on the homo oeconomicus conception: an individual who has well defined goals, determined only by his own needs. Opposite to such a conception is homo sociologicus, an idea of an individual whose actions are determined by social rules. The main idea of this article is that both of them are not able to explain the specifity of economic action which is an example of social action. This situation could draw us to the conclusion that only structural explanations are worth analizing. In this context it means that identyfing main features of structure (market, society, etc.) we make explanation of individual action possible. Finally it appears to be a false solution, too. The only way out of those difficulties is to rebuild basic assumptions of social science, especially because of the uniqueness of its method. Two facts are crucial for the argumentation: first, that social scientist observes reality based on sensible actions (it means, that individuals build interactions on making their actions sensible to others) and second, that theory, being a part of this reality meaning as a process of building sense, could change it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 186-202